Neutralization of toxic activities of Bothrops asper venom by plants of ethnomedical use in Central America: plants collected in Guatemala - Patricia Saravia-Otten; Jose M. Gutierrez; Yann-Oliver Hay; Armando Caceres (Ciencia, Tecnología y Salud, 2022)
There are few scientific studies that explore the use of medicinal plants for snakebite envenoming in Central America, although plant-based therapies have been traditionally used in the region. This work reviews the studies conducted in Central America to assess the ability of extracts obtained from plants of local ethnomedical use to inhibit toxic activities of the venom of Bothrops asper, the snake responsible for approximately half of the snakebite envenomings in these countries. The search prioritized the description of the plants used in Guatemala since most of the studies described in this work were conducted in that country, although references to other countries are included. Information concerning secondary metabolites and other pharmacological activities of these plant species, relevant to the treatment of snakebites, was also described. The literature search was conducted in the Google Scholar, PubMed, and Scopus databases and completed with locally available literature. It was found that extracts of 12 plant species inhibited the hemorrhagic effect of the venom and three neutralized the edema-forming activity, while inhibition of proteolytic and phospholipase A2 (PLA2) activities was achieved by three and one plant species, respectively. Only Brownea rosa-de-monte was able to effectively counteract the in vitro coagulant effect of the venom. Some plant extracts screened in Guatemala demonstrated procoagulant or anti-thrombin intrinsic effects that might aggravate the coagulopathy induced by the venom. These findings underscore the need to carry out scientific studies aimed at validating the inhibitory potential of Central American plant extracts and their metabolites against B. asper venom